Construction of the software and technical complex of control basic parameters of reactor installation - Koba, Kostyantyn; Lys, Stepan; Kravets, Taras; Yurasova, Oksana; Galyanchuk, Igor (Національний технічний університет "Харківський політехнічний інститут", 2022)
The main problem associated with the operation of nuclear power plants is the problem of correct and timely diagnosis of failure or violation. The mistakes of technologists can lead to severe damage to nuclear power plants, or simply to a reduction in the utilization rate of installed capacity. The personnel make the main mistakes in the conditions of time shortage and being in a stressful situation during the development of an accident, when assessing changes in emergency parameters is not always possible, which leads to incorrect diagnosis of initial events (IE). Any IE leads to the deviation of the monitored parameters from normal values (values that are inherent to normal operation). The operator-technologist needs as soon as possible to determine the parameter (or parameters) for which the change occurs and, by performing a certain sequence of actions, bring their values to the norm. For information support of the operator-technologist is the information computing system (ICS). In the ICS, it is possible to control all parameters affecting the safe operation of the equipment, for each of which there are certain values, the deviation from which may lead to an accident. The paper considers the issues of the need to separate the measured parameters of NPP into separate groups that uniquely characterize the state of the critical security features. In particular, the necessity of consideration as the most important mass parameter of the primary coolant is shown. The issues of level measurement problems in the pressure compensator are discussed as the most important from the point of view of determining the mass of the primary coolant. Methods are proposed for determining the operability of sensors, the method of calculating a reliable level in the volume compensator. Estimates of the computational efficiency of the proposed methods are given.

Основною проблемою, пов'язаною з експлуатацією АЕС, є проблема правильного і своєчасного діагностування відмови або порушення. Помилки операторів-технологів можуть призводити, як до важких пошкоджень ядерних енергетичних установок (ЯЕУ), так і просто до зниження коефіцієнта використання встановленої потужності (КВВП). Основні помилки персонал здійснює в умовах дефіциту часу і перебуваючи в стресовій ситуації під час розвитку аварії, коли оцінити зміни аварійних параметрів не завжди можливо, що тягне за собою неправильне діагностування вихідних подій (ВП). Будь-які ВП призводять до відхилення контрольованих параметрів від нормальних значень (значень, які властиві для нормальної експлуатації). Оператору-технологу необхідно в найкоротші терміни визначити параметр (або параметри), за якими відбувається зміна і шляхом виконання певної послідовності дій привести їх значення до норми. Для інформаційної підтримки оператора-технолога служить інформаційно обчислювальна система (ІОС). В ІОС є можливість контролю всіх впливаючих на безпечну роботу устаткування параметрів, для кожного з яких є певні значення, відхилення від яких, може призвести до аварії. В роботі розглянуті питання необхідності виділення вимірювальних параметрів ЯЕУ в окремі групи, які однозначно характеризують стан критичних функцій безпеки (КФБ). Зокрема показано необхідність розгляду, як найбільш важливого параметра, маси теплоносія першого контуру. Порушені питання проблем вимірювання рівня в компенсаторі тиску, як найбільш важливих з точки зору визначення маси теплоносія першого контуру. Запропоновано методи визначення працездатності датчиків, методику розрахунку достовірного рівня в компенсаторі об'єму. Дано оцінку обчислювальної ефективності запропонованих методів.
Побудова програмно-технічного комплексу контролю основних параметрів реакторної установки
Keywords: nuclear power plants; information and computing system; coolant mass; installed capacity utilization factor; initial events; operator-technologist; ядерні енергетичні установки; маса теплоносія; коефіцієнт використання встановленої потужності; вихідні події; оператор-технолог; інформаційно обчислювальна система